Road Traffic Noise Pollution and its Management in Tanjong Malim, Perak - Abdul Rahim, Luqmanulhakim; Hashim, Mohmadisa; Nayan, Nasir (Journal of Techno-Social, 2011)
The increasing number of motorized vehicles in the roads especially in the populated area are the major contributor for noise pollution. This research aimed to study the problem of traffic noise in the town of Tanjong Malim, Perak Darul Ridzuan. For this purpose, a total of nine randomly selected research stations covering the main streets, business center, school and the populated areas were randomly selected. Measurement and observation of level of noise parameters have been using the equipment called Integrating Sound Level data logger Extech Instruments Model 407780. The observations made were at least ten minutes for every observation time for the morning (between 8.00 am-10.00 am), noon time (between 12.00 noon-2.00 pm), evening (between 5.00pm-7.00pm) and night (between 10:00 pm-12.00malam) which covers weekdays and the weekends. The results showed that all value at the all stations is exceeded the standards set by the Department of Environment Malaysia; the noise level 65 dBA for the daytime and 55 dBA for the night-time. Passage area in front of North Gate UPSI recorded the existing Leq 76.6 dBA the highest existing Leq values compared to other nine stations on weekdays observation. Weekend observations recorded value almost similar to the days of the highest noise level recorded in the same way in front of the main door UPSI (74.8 dBA). Various other factors also contribute to traffic noise in the town of Tanjong Malim, such as the proximity of a close to main roads, the higher number of heavy vehicles routing, the estate of vehicle engine and so on. Various mitigation measurement should be considered to negotiate this problem including the sound management aspect, awareness campaign through education, physical construction of natural fortress such as by planting trees between the noise provenance and receiver, efficient traffic management and by law enforcement.